The Diversity of Macrofungi in TWA Gunung Tunak, Central Lombok - Sulastri, Meilinda Pahriana; Andini, Arista Suci; Basri, Hasan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nature Tourism Parks (TWA) Gunung Tunak primarily serves the purpose of nature conservation, emphasizing ecotourism due to its stunning coastal landscapes. Currently, there is a significant lack of documented information regarding the diversity and potential of macrofungi in this protected area. This study aims to assess the diversity of macrofungi found within TWA Gunung Tunak and explore their potential applications. The research was conducted using the line transect and plot method, with samples collected along three transect lines in the study area. Each transect comprised ten plots, each measuring 10 x 10 meters and spaced 10 meters apart. The data collected were analyzed using the Shannon Wiener Diversity Index (H'). A total of 11 species of macrofungi from six families were identified: Polyporaceae, Irpicaceae, Hymenochaetaceae, Gloeophyllaceae, Stereaceae, and Xylariaceae. The family Polyporaceae had the highest representation, with five species (Hexagonia sp., Trametes sp., Microporus sp., Daedalopsis sp., and Podofomes sp.), followed by Hymenochaetaceae, which included the species Phylloporia sp. and Phellinus sp. The remaining families were represented by only one species each, including Irpicaceae (Irpex sp.), Gloeophyllaceae (Gloeophyllum sp.), Stereaceae (Stereum sp.), and Xylariaceae (Xylaria sp.). The diversity index indicates a moderate level of macrofungal diversity from all the trails in the study area, influenced by environmental factors such as temperature, seasonal changes, moisture, and rainfall. Furthermore, the study highlights the potential of these macrofungal species as sources of medicinal and nutritional value.